The relationships between blood pressure, blood glucose, and bone mineral density in postmenopausal Turkish women - ENHOŞ, ASIM; Cakmak, Huseyin Altug; Cakmak, Burcu Dincgez; Yumru, Ayse Ender; Aslan, Serkan; Enhos, Asim; Kalkan, Ali Kemal; İNCİ COŞKUN, EBRU; Acikgoz, Abdullah Serdar; Karatas, Suat (My University, 2015)
Background: Hypertension, diabetes mellitus, and osteoporosis are important comorbidities commonly seen in postmenopausal women. The aim of the present study was to investigate the relationships between blood pressure, blood glucose, and bone mineral density (BMD) in postmenopausal Turkish women.